Autoradiographic determination of the location of radioactivity in asci grown on some tritiated pyrimidines - D. Baer; P. St. Lawrence (Fungal Genetics Reports, 1964)
Autoradiographic determination of the location of radioactivity in asci grown on some tritiated pyrimidines